2021
DOI: 10.3390/cancers13143510
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cartilage Oligomeric Matrix Protein and Golgi Protein-73: New Diagnostic and Predictive Tools for Liver Fibrosis and Hepatocellular Cancer?

Abstract: The cartilage oligomeric matrix protein (COMP) and Golgi-protein-73 (GP73) have been proposed as markers of liver fibrosis and hepatocellular carcinoma (HCC). Our aim was to assess the performance of the combination of these markers in diagnosing cirrhosis and predicting HCC development. Sera from 288 consecutive patients with chronic liver diseases were investigated by using COMP and GP73-ELISAs. Dual positivity for COMP (>15 U/L) and GP73 (>20 units) was observed in 24 (8.3%) patients, while 30 (10.4%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Gatselis et al. reported that the combination of GP73 and the cartilage oligomeric matrix protein (COMP) seems efficient to detect the development of HCC in patients with chronic liver diseases [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gatselis et al. reported that the combination of GP73 and the cartilage oligomeric matrix protein (COMP) seems efficient to detect the development of HCC in patients with chronic liver diseases [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“… 28 In individuals with cirrhosis who had not undergone liver biopsy, the diagnosis was based on clinical findings of decompensated disease, and/or supportive ultrasonography (coarse echo pattern of the parenchyma in association with irregular hepatic margins, spleen >12 cm, portal vein >16 mm), and/or liver stiffness measurements (LSM) using FibroScan® 502 (Echosens, Paris, France) >9 kPa, and/or endoscopic findings of portal hypertension, as we have reported recently. 29 , 30 …”
Section: Methodsmentioning
confidence: 99%
“…Elevated serum COMP is strongly associated with hepatocellular carcinoma (HCC) progression [ 95 ], suggesting that it can be used for non-invasive assessments of HCC progression. Moreover, the combination of COMP and GP73 showed a pronounced performance in detecting severe fibrosis/cirrhosis and predicting the development of HCC in patients with chronic liver diseases [ 30 ]. A recent study also showed that a multi-marker panel (AFP and PIVKA-II, with either IGFBP3, COMP or MMP3, plus age and sex) is efficient for the detection of early- and all-stage HCC [ 96 ].…”
Section: Comp and Cancer/cancer Malignancy/cancer Progressionmentioning
confidence: 99%
“…Serum COMP has been demonstrated to be a sensitive non-invasive diagnostic biomarker for liver fibrosis [ 122 ]. Gatselis et al discovered that serum COMP is efficient to detect cirrhosis in the patients with chronic liver diseases [ 30 ].…”
Section: Comp and Fibrosismentioning
confidence: 99%
See 1 more Smart Citation